Principles of Manual Therapy - Deepak Sebastian (Author) (New Delhi, India, Jaypee Brothers Medical Publishers (P) Ltd, 2019)
Complete guide to manual therapy for physiotherapists. Fully revised, third edition with new topics included. Authored by Michigan-based expert in the field. Previous edition (9789350903049) published in 2012.
PART 1: A Manual Therapy Approach to Musculoskeletal DysfunctionSection 1: Introduction and PrinciplesIntroductionThe Evolution of the Practice of Manual TherapyManipulation: Definition and TypesUnderstanding Mechanical DysfunctionPrinciples of Management of Mechanical DysfunctionPalpationPrinciples of Diagnosis Section 2: Spinal ManipulationCervical SpineThoracic Spine and RibsLumbar SpineThe Pelvic Complex 1 Section 3: Extremity ManipulationAnkle and FootKneeHipShoulderElbowWrist and Hand PART 2: A Manual Therapy Approach to Mechanical Peripheral Nerve Entrapment DysfunctionIntroductionRelevant AnatomyUnderstanding Mechanical Nerve DysfunctionExaminationTreatment PART 3: Regional Conditions and Relevant Manual Therapy InterventionCervical RegionThoracic RegionLumbopelvic RegionHip RegionKnee RegionAnkle and Foot RegionShoulder RegionElbow, Wrist and Hand Region PART 4: The Critical and Neglected Zones of the Upper and Lower Quarter in the Management of Regional ConditionsThe Upper QuarterThe Lower Quarter Index
Keywords: Manipulation (Therapeutics)